2015
DOI: 10.1111/rode.12187
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Foreign Direct Investment on Income Convergence in China after Early 1990s from a Spatial Econometric Perspective

Abstract: This paper introduces foreign direct investment (FDI) as an endogenous variable based on a neoclassical model of economic growth and investigates the impact of FDI on income convergence in China using provincial panel data from 1991 to 2007. A spatial model is later exploited to further examine the effect of FDI on convergence in China in light of remarkable and positive spatial correlations among neighboring regions. Results of estimates confirm the role of FDI inflow as a significant driving force to promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
2
5
0
1
Order By: Relevance
“…Given the sample average value of FDI (0.013) and GINI variable (0.283), we can expect that a 10% increase in FDI to provincial GRP ratio brings about a 0.016 decrease in intra-provincial inequality (measured by GINI coefficient), ceteris paribus 11 . The result corroborates the findings of Gries and Redlin ( 42 ), and Ma and Jia ( 39 ). However, our finding differs from studies based on inter-provincial data [e.g., ( 35 , 37 )] and prefectural-level cities data ( 19 ) documenting that FDI increases inequality.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Given the sample average value of FDI (0.013) and GINI variable (0.283), we can expect that a 10% increase in FDI to provincial GRP ratio brings about a 0.016 decrease in intra-provincial inequality (measured by GINI coefficient), ceteris paribus 11 . The result corroborates the findings of Gries and Redlin ( 42 ), and Ma and Jia ( 39 ). However, our finding differs from studies based on inter-provincial data [e.g., ( 35 , 37 )] and prefectural-level cities data ( 19 ) documenting that FDI increases inequality.…”
Section: Resultssupporting
confidence: 91%
“…Huang and Wei ( 19 ) and Zhang et al ( 20 ) find that FDI contributes to income inequality and the formation of convergence clubs across prefectural-level Chinese cities. On the contrary, Ma and Jia ( 39 ) document a positive association between FDI and regional income convergence.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Lin et al (2011) introduced the panel cointegration model using province-level panel data from 1997 to 2006 to empirically explore the effect of FDI on Total Factor Productivity (TFP) across regions in China.Its empirical result found the spillover effects of FDI inflow may markedly result in economic growth and technological advancement in China for both short and long period within and cross regions. Ma and Jia (2015) stated that the effect of FDI on income inequality has been examined by the neoclassical model of convergence and the augmented model with FDI introduced using provincial panel data for three periods : 1978-2007, 1978-1990 and 1991-2007. They found that during 1978-1990, regional economic growth showed a convergence trend while during 1991-2007, its growth rate became divergence (Ma & Jia, 2015).…”
Section: Methodologies On Researching Fdi and Regional Economic Growthmentioning
confidence: 99%
“…Recent studies have shown that FDI is one of the main driving forces for regional economic growth and income convergence (Choi, 2004;Ma & Jia, 2015). In terms of empirical research on China, Wei (2002) discussed the impact of FDI on regional economic growth of coastal and interior areas using time series and cross-section data from 1985 to 1999, and found that FDI inflow has made a great contribution to the vast majority of regional economic growth gap between these two areas.…”
Section: Fdi and Related Growth Factorsmentioning
confidence: 99%